Lawsuits in Pauls theological ethics : a historical and literary interpretation of 1 Corinthians 6:1-11 - Oh, JungHwan (Stellenbosch : Stellenbosch University, 2014)
Thesis (PhD)--Stellenbosch University, 2014.